The recovery experiences of individuals with schizophrenia in northwestern Ethiopia - Kassa, Selamawit; Ghahari, Setareh; Lysaght, Rosemary; Marshall, Carrie Anne; Mengstie, Missaye Mulatie (Frontiers in Psychiatry, 2025)
IntroductionSchizophrenia recovery is perceived as a one-time symptom remission. However, it is a process that may continue throughout an individual's life. Understanding the recovery experience of a person with schizophrenia is an essential component of filling the mental health service gap and enhancing a smooth recovery process. The objective of this study was to explore the recovery experience of individuals with schizophrenia in a developing country.MethodsTo understand these experiences, we used qualitative research. Seventeen participants were purposefully selected from two hospitals in Northwestern Ethiopia. Semi-structured, in-depth interviews were conducted, and data was analyzed using Interpretive Phenomenological Analysis.ResultsFinally, four themes were generated: the first theme was the meaning of recovery. The definition of schizophrenia recovery differs from person to person based on their personal experience. For some, recovery means becoming free of symptoms, and for others, helping their family and being economically independent. The second theme was obstacles to recovery. The obstacles included limited understanding from family members, decreased social engagement, financial dependency, hopelessness, and suicidal thoughts. The third theme was support by family and employers. Participants received support from people around them. Family members mainly provided support by feeding, clothing, giving medications, and taking them to spiritual places. The fourth theme was coping strategies used to manage illness, which included medication adherence, visiting holy water sites and traditional healers, and listening to spiritual lessons.ConclusionGenerally, participants focused on recovery from illness by emphasizing being free from symptoms to start their regular life. However, some of them were interested in pursuing education and engaging in work. The meaning given for recovery determines the kind of recovery process individuals have. Accepting that schizophrenia is a lifelong disorder, following medical treatments, finding ways to be active in their social life, and engaging in day-to-day activities are crucial components of recovery. In addition, since support from family members is vital, creating awareness creation programs for family members and the community is essential. Finally, psychosocial support and vocational training are important strategies that need to be considered to support recovery.